2000
DOI: 10.1046/j.1469-8137.2000.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal fungi have a potential role in soil carbon storage under elevated CO2 and nitrogen deposition

Abstract: In this review, we discuss the potential for mycorrhizal fungi to act as a source or sink for carbon (C) under elevated CO # and nitrogen deposition. Mycorrhizal tissue has been estimated to comprise a significant fraction of soil organic matter and below-ground biomass in a range of systems. The current body of literature indicates that in many systems exposed to elevated CO # , mycorrhizal fungi might sequester increased amounts of C in living, dead and residual hyphal biomass in the soil. Through this proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
213
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(225 citation statements)
references
References 90 publications
12
213
0
Order By: Relevance
“…This is in contrast to the effects of elevated CO 2 on ectomycorrhizal fungi shown in pot experiments (Godbold et al, 1997). In a review of the effects of elevated CO 2 on mycorrhizal biomass it was concluded that elevated CO 2 predominately increases or has no effect on mycorrhizal hyphal biomass (Treseder and Allen, 2000). The increase in mycorrhizal hyphal biomass was often associated with a shift in mycorrhizal species assemblage, an effect that was not seen at EuroFACE due to the low species diversity (Lukac et al, 2003).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is in contrast to the effects of elevated CO 2 on ectomycorrhizal fungi shown in pot experiments (Godbold et al, 1997). In a review of the effects of elevated CO 2 on mycorrhizal biomass it was concluded that elevated CO 2 predominately increases or has no effect on mycorrhizal hyphal biomass (Treseder and Allen, 2000). The increase in mycorrhizal hyphal biomass was often associated with a shift in mycorrhizal species assemblage, an effect that was not seen at EuroFACE due to the low species diversity (Lukac et al, 2003).…”
Section: Resultsmentioning
confidence: 92%
“…Ectomycorrhizal and AM fungi both contain relatively recalcitrant compounds, chitin and glomalin respectively, which are specific to fungi. Glomalin has been suggested to contribute strongly to SOM (Treseder and Allen, 2000), and have a residence time in soils of 6-42 years (Rillig et al, 2001). Similarly, chitin contents of ectomycorrhizal hyphae have been estimated at between 5 and 12% and up to 60% of dry weight (Muzzarelli, 1977;Ekblad et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Early work examining the decomposition of pure chitin in soil microcosms showed that pure chitin is decomposed more rapidly than pure cellulose when added to soil (Trofymow et al, 1983). However, more recently ecologists have suggested that chitin is a recalcitrant polymer in fungal necromass and may result in a large build up of fungal necromass in soil organic matter (SOM) (Treseder and Allen, 2000;Langley and Hungate, 2003;Godbold et al, 2006). One of the problems with decomposition studies is that recalcitrance is not explicitly defined in many cases (see Schmidt et al, 2011).…”
Section: Polysaccharides: Glucans and Chitinmentioning
confidence: 99%
“…The influence of EM fungi on nutrient uptake has been well documented, and its implications for ecosystem processes are now generally appreciated (Read, 1991;Read and Perez-Moreno 2003;Courty et al, 2010;Orwin et al, 2011). In addition, we are beginning to recognize the significance to biogeochemical cycles of inputs resulting from the death of EM fungal tissues (Fogel, 1980;Fogel and Hunt, 1983;Treseder and Allen, 2000;Langley and Hungate, 2003;Godbold et al, 2006;Cairney, 2012;Clemmenssen et al, 2013;Ekblad et al, 2013). Until recently, little attention has been paid to EM fungal necromass inputs due to the fact that microbial necromass inputs have been considered to be relatively insignificant as standing pools of microbial biomass are often relatively small compared to those of standing plant biomass.…”
Section: Introductionmentioning
confidence: 99%
“…First, we hypothesized that more diverse systems would have greater TBCA because complementary resource use results in greater C fixation and productivity (Tilman and others 1996;Fargione and others 2007). Second, we hypothe-sized that because root production, respiration, exudation, and mycorrhizal allocation tend to increase at elevated CO 2 , likely due to increased photosynthate availability (Matamala and Schlesinger 2000;Treseder and Allen 2000;Pendall and others 2004;Allen and others 2005;Trueman and Gonzalez-Meler 2005), TBCA would increase at elevated CO 2 . However, over time, the CO 2 fertilization effect may create feedbacks that reduce N availability and thus also reduce the stimulation of biomass by elevated CO 2 (progressive N limitation, PNL; Reich and others 2006b).…”
Section: Introductionmentioning
confidence: 99%